Neuroleptic malignant syndrome in an elderly patient with bipolar disorder - Woon, Luke Sy-Cherng; Nazirah A,; Mohd Muhaimin MH,; Hatta Sidi,; Wan Asyraf Wan Zaidi, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Neuroleptic malignant syndrome (NMS) is a well-known and potentially fatal complication of antipsychotic use. The elderly population, with multiple risk factors, are more vulnerable to this condition. We described a case of an 80-year-old man with bipolar disorder, previously on oral extended-release sodium valproate, aripiprazole and long-acting injectable paliperidone, who developed NMS. He presented with generalised muscle rigidity, fever, fluctuating blood pressure and elevated creatinine kinase during his hospitalisation for a manic episode. Contributing factors included old age, underlying vascular Parkinsonism, electrolyte imbalance, intercurrent lung infection with acute exacerbation of chronic obstructive pulmonary disease, hyperactive delirium, and repeated administration of parenteral typical antipsychotic. Antipsychotics were withheld promptly, and the patient was treated with dantrolene, bromocriptine and amantadine. His symptoms resolved after a week. He subsequently remained well with oral extended-release sodium valproate alone. Relevant clinical points are discussed. Clinical vigilance, close interdisciplinary cooperation, and prompt interventions are keys to successful to management of NMS in elderly patients.